2013
DOI: 10.1017/s1368980013000141
|View full text |Cite
|
Sign up to set email alerts
|

Sugar consumption and global prevalence of obesity and hypertension: an ecological analysis

Abstract: Objective: The nutrition transition model provides an integrated approach to analyse global changes in food consumption and lifestyle patterns. Whether variability in food availability for consumption, lifestyle and sociodemographic factors is associated with the worldwide prevalence distribution of overweight, obesity and hypertension is unclear. Design: Ecological analysis. Setting: Country-specific prevalence estimates of overweight, obesity and hypertension were obtained. Prevalence estimates were then mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(68 citation statements)
references
References 54 publications
3
61
0
3
Order By: Relevance
“…This means that errors are reduced but some inaccuracies related to reporting quality may still be present in the data. Similar data from the same sources were recently used to analyse the relationships between nutrients and obesity [31,32] and diabetes [33][34][35] in a number of publications.…”
Section: The World Bank Datamentioning
confidence: 99%
“…This means that errors are reduced but some inaccuracies related to reporting quality may still be present in the data. Similar data from the same sources were recently used to analyse the relationships between nutrients and obesity [31,32] and diabetes [33][34][35] in a number of publications.…”
Section: The World Bank Datamentioning
confidence: 99%
“…This was consistent with the ecological study of the UK and other previous studies. [24][25][26] Also, a Swiss study found a positive association between obesity and salt intake. 27 This was also consistent with the policy and action on nutrition and health promotion in many countries.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to metabolic syndromes, excessive sugar consumption is associated with several types of cancers, including BC (29,30). High sugar consumption in addition to inactive lifestyle is also associated with the higher prevalence of obesity (31). An additional spoon of sugar consumed daily is thought to be associated with 14% increased risk of being overweight or obese (32).…”
Section: Discussionmentioning
confidence: 99%